Association between sex inequality in animal protein intake and economic development in the Papua New Guinea highlands: The carbon and nitrogen isotopic composition of scalp hair and fingernail. Issue 1 (2nd September 2015) - Umezaki, Masahiro; Naito, Yuichi I.; Tsutaya, Takumi; Baba, Jun; Tadokoro, Kiyoshi; Odani, Shingo; Morita, Ayako; Natsuhara, Kazumi; Phuanukoonnon, Suparat; Vengiau, Gwendalyn; Siba, Peter M.; Yoneda, Minoru
ABSTRACT: Objectives: People in the Papua New Guinea Highlands consume sweet potatoes as their dietary staple; consumption of animal protein is limited. In such societies with marginal protein intake, the intra‐household allocation of animal protein in terms of sex or age is of importance. The objective of this study was to investigate how the allocation pattern of protein‐rich foods by sex and age is associated with economic development in the Papua New Guinea Highlands. Methods: The carbon and nitrogen isotopic compositions of fingernails, collected in 1995 in two areas (Tari and Port Moresby [the national capital where Tari migrants resided]), and of scalp hair, collected in 2007, 2012, and 2013 in three areas of different degree of economic development (Levani, Tari, and Goroka) were analyzed. Results: Analysis of fingernail samples showed that δ 15 N was lower in rural communities than in the urban migrant community, while a sex difference in δ 15 N (higher in males than in females) was found in the former but not in the latter community. Age was not associated with either δ 15 N or δ 13 C values. The analysis of scalp hair samples showed that δ 15 N values were lowest in Levani, the least developed area. Furthermore, there were statistically significant sex differences in δ 15 N values in Levani but not in Tari and Goroka. Age was not associated with either δ 15 N or δ 13 C values. Discussion: The sex inequality in animal protein consumption seems to have decreased as the communities in the Papua New Guinea Highlands have experienced economic development. Am J Phys Anthropol 159:164–173, 2016. © 2015 Wiley Periodicals, Inc.